Time Dependence of Aequorin-lndicated Calcium Levels in Stimulated and Unstimulated Platelets: Evidence for Multiple Aequorin Environments in Platelets - Lages, Bruce; Weiss, Harvey J (Thrombosis and Haemostasis, 1989)
Aequorin-induced calcium signals were examined in human unstimulated platelets and platelets stimulated with various agonists as a function of time. The total aequorin response in unstimulated platelets, obtained by Triton x-100 lysis in the presence of 1 mM Ca, decreased in a distinctly non-linear manner over 20-60 min. This decrease was slightly, but significantly, greater in platelets maintained in the continuous presence of 1 mM Ca than in platelets maintained without external Ca, and could not be accounted for completely by leakage of aequorin from the cells. Basal Ca levels in unstimulated platelets also decreased in a non-linear manner, with a similar sensitivity to the contmuous presence or absence of external Ca. These observed changes in aequorin response thus appear to be at least partially due to an mtracellular discharge of aequorin, and are therefore consistent with the view that aequorin in platelets is heterogeneously d1stnbuted among localized environments differing in Ca concentration. The aequorin signals observed initially in platelets stimulated by ADP or epinephrine were lost completely over a penod of 30-60 min in almost all cases studied, while initial rates of aggregation were either unchanged (epinephrine) or only partially decreased (ADP) over this same time period. In contrast, thrombin- and A23187-induced aequorin signals were virtualy unchanged over periods up to 90 min. Minimal changes with time also occurred in the aequorin signals induced by phorbol ester or by collagen in the presence of indomethacin. These differences in time dependence suggest that the signals generated by ADP and epinephrine may derive from different sources of aequorin than those associated with the signals induced by other agonists. Thus, differences in indicator localization may indeed contnbute to the observation of aequorin, but not quin 2/fura-2, signals following epinephrine stimulation as previously suggested, but this may not be the sole explanation for the discrepancies between these two Ca indicators seen with other agonists.
Keywords: Platelet calcium; Aequorin; Calcium mobilization